A Combined Viscous-Steel Damping System (CVSDS) for Longitudinal Vibration Mitigation of A long-span Railway Suspension Bridge. Issue 5 (4th April 2023) - Hu, Shangtao; Meng, Dongliang; Hu, Renkang; Yang, Menggang
ABSTRACT: To mitigate longitudinal vibration of long-span railway suspension bridges, a Combined Viscous-Steel Damping System (CVSDS) is put forward in this paper. In the CVSDS, the viscous damper is expected to work under train braking and frequent earthquakes, while the steel damper can resist rare earthquakes. Moreover, a fuse-lock device is proposed to work as the switch between the aforementioned two dampers. The working mechanism of the CVSDS was introduced. The locking function was verified by static test, and the vibration reduction efficiency of the proposed system was validated through numerical method. The results show that the combined system is efficient.